Identity Politics and Religious Recognition in Indonesian Democracy: A Post-Secular Perspective - Jegalus, Norbertus (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
In various academic literature studies in Indonesia, identity politics is often equated with the politicization of identity. As a result, ​​identity politics is less noticed as the politics of recognition or multiculturalism politics for oppressed identity groups. This article aims to show the distinction between identity politics and politicization of identity in the history of democracy in Indonesia, while also showing how identity politics, as the politics of recognition and religious moral values, ​​can support democratization. This study is a philosophical research and therefore uses a philosophical research methodology, with five main methodological elements: Interpretation, internal coherence, holistic, historical continuity, and heuristics. First, this study finds that Identity politics and politicization of identity are two terms in contemporary social philosophy with different meanings. Identity politics is not bad per se, while politicization of identity is harmful per se; second, the answer to the problem of democracy is not to confine religion to the private sphere as in secularism in the West or the depoliticization of Islam in the New Order era in Indonesia, but rather to carry out a double learning process between state and religion, politics and faith, reason and revelation, which is called post-secularism; Third, religious hegemony remains a threat to democracy in Indonesia, but because democracy is not only a system but also an ethos, the moral contribution of religion is greatly needed in forming a healthy democracy. In conclusion, identity politics can support democracy when religion engages in dialogue with public reason and becomes the moral foundation of the democratic ethos. Therefore, this study suggests that religion and state must always engage in a dual learning process and recognize each other's contributions.